Biodegradative capacity of filamentous fungi against polyethylene in geographic height - Gonzales-Alcos, Vicky; Cervantes-Alagon, Sheyla; Huarachi-Valencia, Juan; Casa-Coila, Manuela (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
The biodegradation of polyethylenes by microorganisms is a solution for the reduction of contamination by plastics, constituting an important alternative from the point of view of human health, the environment and the economic factor; The purpose of this research was to determine the biodegradability of filamentous fungi against polyethylene; the fungi were isolated from solid plastic waste obtained from the Cancharani dump, taxonomic identification of filamentous fungi with degradative capacity against polyethylene was carried out on the basis of macroscopic characteristics of plate growth and microscopic study using the Microculture sheet technique; The degradative capacity was determined at pH 5 and 20 ° C for 20 days and to determine the pH and temperature conditions where filamentous fungi with biodegradative capacity achieve greater activity against polyethylene was performed using the Kavelman and Kendrick technique at temperatures of 20 and 30 ° C and at pH 4.5 and 8.0. Five species of filamentous fungi were isolated; Aspergillus Flavus, Aspergillus niger, Aspergillus fumigatus, Mucor sp. and Fusarium sp, resulting in having biodegradative capacity at different rating scales and are statistically biodegradable against polyethylene. Aspergillus flavus also showed a greater biodegradability compared to Aspergillus niger at a pH of 4.5, the temperature being indifferent at 20 and 30 ° C, Statistically, both are good biodegradators against polyethylene, which highlights the importance of this research.